If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3ln(2x) + 1 = 5 Remove parenthesis around (2x) 3ln * 2x + 1 = 5 Reorder the terms for easier multiplication: 3 * 2ln * x + 1 = 5 Multiply 3 * 2 6ln * x + 1 = 5 Multiply ln * x 6lnx + 1 = 5 Reorder the terms: 1 + 6lnx = 5 Solving 1 + 6lnx = 5 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 6lnx = 5 + -1 Combine like terms: 1 + -1 = 0 0 + 6lnx = 5 + -1 6lnx = 5 + -1 Combine like terms: 5 + -1 = 4 6lnx = 4 Divide each side by '6nx'. l = 0.6666666667n-1x-1 Simplifying l = 0.6666666667n-1x-1
| 20x+2y=12 | | ln(2x+11)+ln(x-9)-2ln(x)=0 | | 2(-6-3)=-9 | | -6/3=-2 | | 2c+27=5c | | 3a-b-2a+56= | | 2x+3x-3=8 | | .1x+x=3000 | | 9x+45=3(4x-3) | | 5(x-2)+10=5x-25 | | 150a-555= | | 8x+10y=210 | | 3v^3+4v^2+9v+12= | | 1a-46= | | 4=3c-17 | | 2(x-3)=-9 | | a+2a=.08 | | 15/x-2=9/x | | 7x+5=2(3x+12) | | l+4=-2 | | 7(x-2)=3x-2 | | 9-x+8=-6 | | 15=x+12 | | e+-43=-45 | | 4(b-5)+5b(8-6b)= | | 7x+3=2x+58 | | -16(t^2-361)=0 | | 0.3(3n-5)=0.4-0.2(n-7) | | (q-5)*2=10 | | 12xX=72 | | a-52=112 | | (q-8)*3=6 |